Typing of Canine Parvovirus Strains Circulating in North‐East China. Issue 2 (19th July 2015) - Zhao, H.; Wang, J.; Jiang, Y.; Cheng, Y.; Lin, P.; Zhu, H.; Han, G.; Yi, L.; Zhang, S.; Guo, L.; Cheng, S.
Summary: Canine parvovirus (CPV) is highly contagious and is a major cause of haemorrhagic enteritis and myocarditis in dogs. We investigated the genetic variation of emerging CPV strains by sequencing 64 CPV VP2 genes from 216 clinical samples of dogs from Heilongjiang, Jilin, Liaoning, Shandong and Hebei in 2014. Genetic analysis revealed that CPV‐2b was predominant in Hebei and CPV‐2a was predominant in the other four provinces. In addition, a CPV‐2c strain has emerged in Shandong province. All samples had a Ser‐Ala substitution at residue 297 and an Ile‐Arg substitution at residue 324. Interestingly, in five separate canine samples, we found a mutation of Gln370 to Arg, until now detected only in isolates from pandas. The phylogenetic analysis showed clear distinctions between epidemic isolates and vaccine strains and between Chinese CPV‐2c strains and CPV‐2c strains found in other countries. Monitoring recent incidence of CPV strains enables evaluation and implementation of disease control strategies.